Effects of transcranial direct current stimulation on brain cytokine levels in rats - Ethridge, Victoria T.; Gargas, Nathan M.; Sonner, Martha J.; Moore, Raquel J.; Romer, Shannon H.; Hatcher-Solis, Candice; Rohan, Joyce G. (Frontiers in Neuroscience, 2022)
Transcranial direct current stimulation (tDCS) has shown therapeutic potential to mitigate symptoms of various neurological disorders. Studies from our group and others used rodent models to demonstrate that tDCS modulates synaptic plasticity. We previously showed that 30 minutes of 0.25 mA tDCS administered to rats induced significant enhancement in the synaptic plasticity of hippocampal neurons. It has also been shown that tDCS induces expression of proteins known to mediate synaptic plasticity. This increase in synaptic plasticity may underly the observed therapeutic benefits of tDCS. However, the anti-inflammatory benefits of tDCS have not been thoroughly elucidated. Here we report that three sessions of tDCS spaced 1-3 weeks apart can significantly reduce levels of several inflammatory cytokines in brains of healthy rats. Rats receiving tDCS experienced enhanced synaptic plasticity without detectable improvement in behavioral tests or significant changes in astrocyte activation. The tDCS-mediated reduction in inflammatory cytokine levels supports the potential use of tDCS as a countermeasure against inflammation and offer additional support for the hypothesis that cytokines contribute to the modulation of synaptic plasticity.